Human cytomegalovirus immediate-early 1 protein facilitates viral replication by antagonizing histone deacetylation - Nevels, Michael (National Academy of Sciences, 2004)
The human cytomegalovirus 72-kDa immediate-early (IE)1 and 86-kDa IE2 proteins are expressed at the start of infection, and they are believed to exert much of their function through promiscuous transcriptional activation of viral and cellular gene expression. Here, we show that the impaired growth of an IE1-deficient mutant virus in human fibroblasts is efficiently rescued by histone deacetylase (HDAC) inhibitors of three distinct chemical classes. In the absence of IE1 expression, the viral major IE and UL44 early promoters exhibited decreased de novo acetylation of histone H4 during the early phase of infection, and the hypoacetylation correlated with reduced transcription and accumulation of the respective gene products. Consistent with these findings, IE1 interacts specifically with HDAC3 within infected cells. We also demonstrate an interaction between IE2 and HDAC3. We propose that the ability to modify chromatin is fundamental to transcriptional activation by IE1 and, likely, IE2 as well.